Association of daily and time-segmented physical activity and sedentary behaviour with mental health of school children and adolescents from rural Northeastern Ontario, Canada - da Costa, Bruno G. G.; Bruner, Brenda; Raymer, Graydon H.; Benson, Sara M. Scharoun; Chaput, Jean-Philippe; McGoey, Tara; Rickwood, Greg; Robertson-Wilson, Jennifer; Saunders, Travis J.; Law, Barbi (Frontiers in Psychology, 2022)
Physical activity (PA) and sedentary behaviour (SED) have been linked to the mental health of children and adolescents, yet the timing of behaviours may play a role in this relationship and clarifying this could inform interventions. We explored cross-sectional associations of PA and SED in varying time segments throughout the school day with the mental health of school-aged children and adolescents from rural Northeastern Ontario, Canada. A total of 161 students (56% female, M = 10.3 years old) wore accelerometers for 8 days (7 nights) and completed a self-report survey (parent reported for children younger than 11). Mental health was measured using the Strengths and Difficulties Questionnaire. Accelerometer-measured SED, light PA (LPA), and moderate and vigorous PA (MVPA) were estimated in the time-segments before school (06:00-08:44), school time (08:45-15:04), after school (15:05-16:59), and evenings (17:00-21:59). Associations were tested with multilevel linear regressions while adjusting for confounding factors. Students spent 72.6 minutes in MVPA, 209.0 minutes in LPA, and 621.0 minutes in SED per day. Daily SED was associated with less conduct problems (β=-0.27, p<0.05). Evening LPA was inversely associated with hyperactivity (β=-1.45, p<0.05), while SED was associated with hyperactivity and with peer problems before school (β=1.70 and β=1.01, respectively, p<0.05), and during school (β=-0.83 and β=-0.57, respectively, p<0.05). No associations were observed for MVPA, emotional symptoms, or prosocial behaviour. In conclusion, displacing SED with LPA in some specific periods of the day may benefit the mental health of students; taking this into account could strengthen interventions.